(untitled) (Arquivos em Odontologia, 2023)
Aim: This study aimed to evaluate the respiratory parameters among patients diagnosed with severe obstructive sleep apnea (OSA) syndrome treated with a novel design of an oral appliance (OA): a lingual orthosis. Methods: A case series study was conducted with 11 patients suffering from severe OSA, apnea-hypopnea index (AHI) > 30 events/h. All patients underwent pre- and post-treatment overnight polysomnography and were diagnosed by a physician based on polysomnography indexes. All selected patients had a history of nonadherence to continuous positive airway pressure devices. Results: Before treatment, the mean AHI of the sample was 65.9 ± 30.5. After reaching the optimal OA titration, the polysomnography (PSG) showed an average AHI of 10.1 ± 5.5 (p<0.001). There was a significant reduction in obstructive events that decreased from 60.0 ± 31.7 to 8.5 ± 3.8 events/hour (p<0.001). The minimal oxyhemoglobin saturation showed significant improvement after the OA treatment, increasing from 74.3 ± 7.8 to 83.4 ± 4.9 (p<0.05). Conclusion: Lingual orthosis was effective in resolving severe OSAS, showing satisfactory results within the present sample. Further studies are needed in order to broaden the knowledge regarding the effectiveness of this oral appliance.